Isomerization of Allylic Alcohols to Ketones Catalyzed by Well‐Defined Iron PNP Pincer Catalysts. Issue 16 (16th January 2018) - Xia, Tian; Wei, Zhihong; Spiegelberg, Brian; Jiao, Haijun; Hinze, Sandra; de Vries, Johannes G.
Abstract: [Fe(PNP)(CO)HCl] (PNP=di‐(2‐diisopropylphosphanyl‐ethyl)amine), activated in situ with KO t Bu, is a highly active catalyst for the isomerization of allylic alcohols to ketones without an external hydrogen supply. High reaction rates were obtained at 80 °C, but the catalyst is also sufficiently active at room temperature with most substrates. The reaction follows a self‐hydrogen‐borrowing mechanism, as verified by DFT calculations. An alternative isomerization through alkene insertion and β‐hydride elimination could be excluded on the basis of a much higher barrier. In alcoholic solvents, the ketone product is further reduced to the saturated alcohol. Abstract : A borrowing pincer : The isomerization of non‐activated allylic alcohols to ketones catalyzed by an iron(II) PNP pincer complex (see graphic) is reported. High reaction rates have been achieved, even at room temperature. A self‐borrowing hydrogen mechanism has been established on the basis of DFT calculations.